Fines, Leniency and Rewards in Antitrust: An Experiment - Maria Bigoni; Sven-Olof Fridolfsson; Chloé Le Coq; Giancarlo Spagnolo (Research Institute of Industrial Economics (IFN), 2008)
This paper reports results from an experiment studying how fines, leniency programs and reward schemes for whistleblowers affect cartel formation and prices. Antitrust without leniency reduces cartel formation, but increases cartel prices: subjects use costly fines as (altruistic) punishments. Leniency further increases deterrence, but stabilizes surviving cartels: subjects appear to anticipate harsher times after defections as leniency reduces recidivism and lowers post-conviction prices. With rewards, cartels are reported systematically and prices finally fall. If a ringleader is excluded from leniency, deterrence is unaffected but prices grow. Differences between treatments in Stockholm and Rome suggest culture may affect optimal law enforcement.
Keywords: C73; C92; L41; 330; Cartels; Collusion; Coordination; Competition policy; Deterrence; Desistance; Law enforcement; Price-fixing; Punishment; Recidivism; Whistleblowers; Organisierte Kriminalität; Kartellrecht; Strafe; Straffreiheit; Test; Spieltheorie